IMPLEMENTATION OF COMMUNITY-BASED EYE HEALTH POLICY THROUGH GLAUCOMA EDUCATION AMONG THE SEMA’AN AL-QUR’AN GROUP - Sahli, Muhamad; Mu’tafi, Ali (LPPM Univ. Ibn Khaldun Bogor, 2026)
Glaucoma is one of the leading causes of irreversible blindness worldwide and remains a major public health problem, particularly among the elderly population. Its slow and often asymptomatic progression in the early stages results in late diagnosis, emphasizing the importance of preventive and early detection strategies. This community service activity aimed to improve knowledge and understanding of glaucoma among members of the Sema’an Al-Qur’an group in Sindupaten Village, Kertek District, Wonosobo, through a community-based health promotion approach. The intervention consisted of interactive health education sessions, discussions, question-and-answer activities, and the use of educational media, including PowerPoint presentations, leaflets, and posters. Knowledge levels were assessed using pre-test and post-test questionnaires administered to 10 participants, most of whom were elderly. The results demonstrated a significant increase in the mean knowledge score from 78 in the pre-test to 98 in the post-test, with the minimum score improving from 40 to 80. Furthermore, 90% of participants achieved a very good level of knowledge after the intervention. These findings indicate that community-based health education is effective in enhancing glaucoma-related health literacy. This program supports the implementation of eye health policies by strengthening promotive and preventive efforts at the primary healthcare level, thereby contributing to early detection and reducing the risk of permanent blindness due to glaucoma.